Endobronchial ultrasound: launch of an ERS structured training programme - Farr, Amy; Clementsen, Paul Frost; Herth, Felix; Konge, Lars; Rohde, Gernot; Dowsland, Sarah; Schuhmann, Maren; Annema, Jouke (Breathe, 2016)
Tweetable abstract ERSpublications - click to tweetERS launches structured EBUS training programme http://ow.ly/br5P302vhh3
Gesehen am 13.05.2020